2019
DOI: 10.3892/etm.2019.7376
|View full text |Cite
|
Sign up to set email alerts
|

Felodipine‑associated gingival overgrowth in a type 2 diabetic patient: A case report and literature review

Abstract: Gingival overgrowth (GO) includes gingival enlargement and hyperplasia and may be induced by certain drugs, including calcium channel blockers (CCBs), particularly first-generation CCBs. However, to date, only few cases of GO induced by second- or third-generation CCBs have been reported. The present study reports on a case of a 48-year-old diabetic male who was admitted to the First Hospital of Jilin University (Changchun, China) due to poor blood glucose control. This patient was diagnosed with GO. Review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Several studies attempted drug discontinuation and/or non-surgical periodontal therapy and reported successful results in terms of management. [ 28 ] A case series published by Routray et al . [ 29 ] in 2003 reported a 15-year-old male taking 5 mg of amlodipine daily for hypertension induced by aortoarteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies attempted drug discontinuation and/or non-surgical periodontal therapy and reported successful results in terms of management. [ 28 ] A case series published by Routray et al . [ 29 ] in 2003 reported a 15-year-old male taking 5 mg of amlodipine daily for hypertension induced by aortoarteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports have also mentioned the association between diabetes and the induction of CCB-induced GO 26 27. Although the mechanism by which diabetes mellitus affects GO remains unclear, it has been hypothesised that hyperglycaemia is related to an increased inflammatory response which may play a role in the pathogenesis of GO 28. Additionally, ‘poor oral hygiene’ is a commonly reported factor in several case reports regarding diabetes and the development of GO, including ours, and is a key factor which causes gingival inflammation.…”
Section: Discussionmentioning
confidence: 99%